Commodification of Disability in Digital CSR Campaigns: Semiotic and Reseption Analysis VCD Students - Nurul Fadhillah S; Sri Riski Wulandari (Jurnal Riset Komunikasi, 2026)
This study aims to analyze the commodification of disability in digital Corporate Social Responsibility (CSR) campaigns and map the reception patterns among Visual Communication Design (VCD) students. Adopting a descriptive qualitative approach, the study employs a multistage analysis integrating Roland Barthes’ semiotics on five CSR campaign videos; Pertamina, Tokopedia, Indodax, BRI Insurance, and Alfamidi, alongside Stuart Hall’s reception theory through reflective discussions with 24 VCD students at Universitas Negeri Makassar. The findings reveal that CSR videos systematically naturalize disability as an emotional commodity, portraying subjects as "empowered" yet confined within frameworks of inspiration and productivity. Meanwhile, VCD students predominantly occupy negotiated and oppositional positions, identifying practices of "inspiration porn" and affective commodification behind ostensibly humanistic narratives. The originality of this research lies in its integration of semiotics and the political economy of media to uncover how audiences with high visual literacy deconstruct hegemonic messages within digital communication structures. Practically, the results suggest the necessity of integrating the ethics of representation into design curricula to cultivate reflective practitioners who avoid exploiting marginal groups. However, this study is limited by its specific participant scope within a single study program; thus, the findings reflect the reception trends of a specific group rather than broad population generalizations.